Reconstruction and Recovery Planning in the Aftermath of Typhoon Haiyan (Yolanda) - World Bank Group (Washington, DC, 2015)
This report summarizes the just-in-time advice provided by the World Bank to the government of the Philippines (GoP) immediately after Typhoon Haiyan. The Bank helped the National Economic and Development Authority (NEDA) develop the Reconstruction Assistance on Yolanda (RAY) plan, providing recommendations and sharing international good practice on key aspects of recovery and reconstruction, including institutional arrangements for recovery implementation, use of remote damage assessment, resilient recovery, and reconstruction of housing, buildings, roads, and other infrastructure. The report is divided into six chapters: 1. Rapid Damage Assessments: Using Remote Sensing Technologies and Risk Information to Help Determine Preliminary Reconstruction Needs 2. Buildings and Infrastructure: Good Practices for Resilient Reconstruction 3. Housing: Lessons Learned from Large-Scale Housing Reconstruction Programs 4. Building Back Better: Restoring Key Sectors, Local Economy, and Livelihoods 5. Roads and Bridges: Enabling Operational Continuity of Lifelines for Evacuation and Post - Disaster Response 6. Institutional Structures: Good Practices and Options for Effective Planning and Implementation of Reconstruction and Recovery. International experience shared through the engagement includes lessons learned from community driven reconstruction in Indonesia and Pakistan; shelter and housing recovery in Haiti; emergency reconstruction in Turkey; resilient infrastructure and hurricane contingency planning in Florida; resilient reconstruction of buildings in California, Haiti, Japan, and Turkey; remote damage assessment in Pakistan; and resilient road and highway management in East Asia and New Zealand.